Pemanfaatan Aplikasi Sistem Informasi Santri di Ma’had Tahfidh Al-Qur’an Putri Al-Amien - Mardhatillah Ahmad; Musleh Wahid (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the use of the Santri Information System application at Ma'had Tahfidh Al-Qur'an Putri. This research uses a qualitative field approach. The methods used are interviews, observation and documentation. Three types of data analysis were used, namely data reduction, data presentation and conclusions. The results of this research are to find out: 1) the use of the Santri Information System application in the female Ma'had Tahfidh Al-Qur'an. 2) supporting and inhibiting factors in using the Santri Information System application at Ma'had Tahfidh Al-Qur'an Putri.